Performance Monitoring, Subordinate’s Felt Trust and Ambidextrous Behavior; Toward a Conceptual Research Framework - Ahmed, Farooque; Soomro, Shuaib Ahmed; Tunio, Fayaz Hussai; Ding, Yi; Qureshi, Naveed Akhtar (Frontiers in Psychology, 2022)
When performance measurement issues strike, organization leaders and their subordinates look for ways to overcome them and address these outcomes that enhance the leader and member relationships. The present research study proposes a performance monitoring framework based on ambidextrous leadership and social exchange theories. It aims to bring benefit for a leader and subordinates in a performance monitoring system. The paper reviews and integrates essential literature on performance management, trust and ambidextrous behaviour. It enumerates the benefits which accompany necessary movement to human resources in the organizations. We have reviewed relevant literature on the themes and underpinned them for managing performance management within the organization. The scholarship provides positive organizational ambidexterity for a leader and member long term performance. The study emphasises individuals psychological foundations that demonstrate trust behaviour and relationship with their leader. Eventually, ambidextrous managers gain steady performance and professional relationships with their subordinates through the electronic performance management (EPM) system. The study shows that ambidexterity benefits organizations, it enhances employees' resources, resulting in enhanced performance that leads to over macro performance of an organization.